2021
DOI: 10.1016/j.jpeds.2021.07.042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Early Feeding on Intestinal Permeability and Inflammation Markers in Infants with Genetic Susceptibility to Type 1 Diabetes: A Randomized Clinical Trial

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Details of the 14 major birth cohorts are provided in online supplemental figure 2 and online supplemental table 2 , which summarizes the commencement date, cohort size, countries of recruitment and eligibility criteria. Only one established cohort, the EDIA intervention trial based in Finland, 49 commenced recruitment in pregnancy, but followed only a small number of mothers and offspring (n=87). 80% of live born children in ENDIA were followed from pregnancy (n=1178) with two-thirds recruited before the third trimester.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the 14 major birth cohorts are provided in online supplemental figure 2 and online supplemental table 2 , which summarizes the commencement date, cohort size, countries of recruitment and eligibility criteria. Only one established cohort, the EDIA intervention trial based in Finland, 49 commenced recruitment in pregnancy, but followed only a small number of mothers and offspring (n=87). 80% of live born children in ENDIA were followed from pregnancy (n=1178) with two-thirds recruited before the third trimester.…”
Section: Discussionmentioning
confidence: 99%
“…Urine was collected for 5 hours. The concentrations of lactulose and mannitol were measured with enzymatic methods (28). The lactulose/mannitol ratio was calculated as the percentage of lactulose excreted in 5 hours/percentage of mannitol excreted in 5 hours.…”
Section: Discussionmentioning
confidence: 99%
“…They visited the study center at the age of 3, 6, 9, and 12 months. The study protocol has been reported previously in detail (28). During the 12 first months of life, 3 (4%) participants developed islet autoimmunity.…”
Section: Methodsmentioning
confidence: 99%
“…Child growth (weight and length) and intestinal function, including lactulose mannitol (LM) ratio, fecal calprotectin, and fecal β-defensin levels, were also measured at given time points. The study design was recently reported ( 25 ). Selected characteristics of the study subjects are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%